THE IMPACT OF AN INCLUSIVE DIGITAL ECONOMY - Permana, Teguh; Puspitaningsih, Andriani (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This research aims to determine the impact of the digital economy. The method used is a descriptive research method. The research results show that the impact of the digital economy has greatly changed the way we work, do business, interact and access services. On the one hand, the digital economy offers great opportunities to increase efficiency, innovation and economic growth. On the other hand, this also brings challenges, especially in terms of access gaps, data protection and changes in the labor market. Countries and the business world need to respond with adaptation measures so that the benefits of the digital economy can be felt evenly